Ethonyms in Hausa - Paul Newman (LibraryPress@UF, 1984)
Hausa ethnonyms, terms indicating a person's origin, ethnic affiliation, or professional or social position, are formed with a prefix ba-in the singujlar and a suffix -aawaa in the plural. This paper provides a detailed specification of the segmental and tonal characteristics of "these ethnonyms and a comprehensive list of currently acceptable forms. The paper illustrates the semi-productive nature of the construction and the imperfect pairing of forms with ba--/-aawaa. The use of ethnonyms to indicate 'supporters or followers of a person' is documented as well as the overlooked functioning of ethnonyms as adjectival qualifiers. The paper explores the relationship between the suffix and the identical suffix found with names of towns and villages. The major conclusion is that ba- and -aawaa are suppletive derivational markers, the former originally denoting 'person ... ', the latter indicating 'community ... '.